2021
DOI: 10.1007/s10864-021-09452-3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Quantitative Analysis of Interteaching

Abstract: Interteaching is a behavioral teaching method that departs from the traditional lecture format (Boyce & Hineline in BA 25:215–226, 2002). We updated and expanded previous interteaching reviews and conducted a meta-analysis on its effectiveness. Systematic searches identified 38 relevant studies spanning the years 2005–2018. The majority of these studies were conducted in undergraduate face-to-face courses. The most common independent variables were manipulations of the configuration of interteaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…The current study replicated the efficacy of IT in a shortened 9-week term format (Gayman et al, 2018). Most applied IT studies have implemented the teaching method over the course of a semester-length class and found it to be effective (see Hurtado-Parrado et al, 2020, for a review). One exception includes a study by Slezak and Faas (2017), which implemented IT over a 1-day probe and found that, although not statistically different than ST, IT led to higher test scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study replicated the efficacy of IT in a shortened 9-week term format (Gayman et al, 2018). Most applied IT studies have implemented the teaching method over the course of a semester-length class and found it to be effective (see Hurtado-Parrado et al, 2020, for a review). One exception includes a study by Slezak and Faas (2017), which implemented IT over a 1-day probe and found that, although not statistically different than ST, IT led to higher test scores.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IT in an online classroom is new, thus there are many avenues of research that have not yet been explored. Although IT has been implemented across a broad range of disciplines (e.g., psychology, nutrition, rehabilitation, engineering, business) the majority of IT studies have been conducted in social science classes (see Hurtado-Parrado et al, 2020 for a review). Additional studies are needed to determine the generalizability of the methods used to other subjects and online classes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonparametric analysis of test performance suggested no statistically significant difference between the two conditions. However, as with much previous interteaching research (Arntzen & Hoium, 2010;Hurtado-Parrado et al, 2022;Saville et al, 2006;Soldner et al, 2015), students generally preferred the preparation guide condition, which represented a more traditional interteaching method.…”
Section: Discussionmentioning
confidence: 80%
“…In interteaching, the preparation-guide component might be presumed to serve as a prompt for rehearsal as well as a permanent product for the other components (e.g., group discussion) and may or may not be graded for accuracy or completion (Filipiak et al, 2010). Based on Boyce and Hineline's (2002) seminal article on interteaching, a preparation guide should include 10 to 20 shortanswer questions (Hurtado-Parrado et al, 2022). These questions may also contain multiple parts and request several responses from students such as a definition, a description of a procedure or phenomenon, and a comparison of one phenomenon versus another.…”
mentioning
confidence: 99%
See 1 more Smart Citation